Genome-wide identification and tissue-specific expression analysis of UDP-glycosyltransferases genes confirm their abundance in cicer arietinum (chickpea) genome - Sharma, Ranu; Rawat, Vimal; Suresh, C. G. (Plos One, 2014)
UDP-glycosyltransferases (EC 2.4.1.x; UGTs) are enzymes coded by an important gene family of higher plants. They are involved in the modification of secondary metabolites, phytohormones, and xenobiotics by transfer of sugar moieties from an activated nucleotide molecule to a wide range of acceptors. This modification regulates various functions like detoxification of xenobiotics, hormone homeostasis, and biosynthesis of secondary metabolites. Here, we describe the identification of 96 UGT genes in Cicer arietinum (CaUGT) and report their tissue-specific differential expression based on publically available RNA-seq and expressed sequence tag data. This analysis has established medium to high expression of 84 CaUGTs and low expression of 12 CaUGTs. We identified several closely related orthologs of CaUGTs in other genomes and compared their exon-intron arrangement. An attempt was made to assign functional specificity to chickpea UGTs by comparing substrate binding sites with experimentally determined specificity. These findings will assist in precise selection of candidate genes for various applications and understanding functional genomics of chickpea.